Combination of Progressive Muscle Relaxation and Cat Stretch Exercise on Adolescents' Hemoglobin - Wijayanti, Heni; Amelia, Poppy Fransisca; Adinatha, Ni Nyoman Maryaningtyas; Kustriyanti, Dwi (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The menstrual period is one of the triggers for adolescents to experience anemia, characterized by a decrease in hemoglobin levels. This study aims to analyze the effectiveness of combining progressive muscle relaxation and cat stretch exercise in improving hemoglobin levels among adolescent girls, a population at high risk of anemia, particularly during menstruation. This study was quasi-experimental with a pretest-posttest design with two group designs in June-August 2023. Fifty adolescent girls meeting the inclusion criteria were selected using purposive sampling and proportionally divided into two groups, the progressive muscle relaxation and cat stretch exercise combination group, and the walking group. The Point of care testing (examinations carried out near the patient outside the laboratory) method measures adolescent hemoglobin and hemodynamic levels before and after the intervention. The intervention was given for 4 weeks with weekly monitoring. Data were analyzed using the paired t-test and Mann-Whitney test. The combination of progressive muscle relaxation and cat stretch exercise was effective in increasing hemoglobin levels in both groups with an average increase of 0.484 and 0.184 respectively, but there was no difference in average hemoglobin in the two groups after the intervention (p-value 0.011 and 0.004). Physical activity, such as either the combination of PMR and cat stretch exercise or walking, was proven effective in increasing hemoglobin levels. These findings suggest that both methods have the potential to serve as simple and affordable interventions for reducing anemia in adolescent girls during menstruation.